2003
DOI: 10.1212/01.wnl.0000095216.89483.a2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of glutamate release and excitotoxicity by adenosine A 2A receptors

Abstract: Because an increased glutamate outflow is thought to play a crucial role in triggering excitotoxic neuronal death, drugs able to regulate glutamate release could be effective for the management of neurodegenerative diseases. In this article, the authors discuss the hypothesis that adenosine A2A receptor antagonists (A2A antagonists) may belong to the aforementioned category. In rats bilaterally lesioned with the excitotoxin quinolinic acid (QA) in the striatum, the A2A antagonist SCH 58261 significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…20 These data suggest that A3 receptors modulate protective responses during ischemic/ hypoxic brain injury. In this study, we found that A3 antagonist MRS1191 attenuated inosine-mediated protection, suggesting the activation of A3 receptors contributes to these protective effects of inosine in the CNS.Purinergic receptors have been reported to regulate glutamate release 21 and the response to excitatory amino acids. 22 We found that ischemia caused glutamate release in the ischemic cortex.…”
mentioning
confidence: 60%
“…20 These data suggest that A3 receptors modulate protective responses during ischemic/ hypoxic brain injury. In this study, we found that A3 antagonist MRS1191 attenuated inosine-mediated protection, suggesting the activation of A3 receptors contributes to these protective effects of inosine in the CNS.Purinergic receptors have been reported to regulate glutamate release 21 and the response to excitatory amino acids. 22 We found that ischemia caused glutamate release in the ischemic cortex.…”
mentioning
confidence: 60%
“…The A2AR located at these terminals can directly regulate the amount and frequency of glutamate release and outflow. 25 Our results suggest that the suppression of glutamate level may be responsible for the neuroprotective effect provided by A2AR deletion against bTBI in the acute stage, as has been described in other models of brain injury. 26 Failure to clear the synaptic cleft of glutamate can overstimulate postsynaptic glutamate receptors, promoting neuronal death.…”
Section: Inactivation Of A2a Receptor Preserves Cognitive Function Ansupporting
confidence: 77%
“…In the CNS, glutamate can be released from presynaptic glutamatergic terminals such as corticostriatal terminals (Obrenovitch and Urenjak, 1997). The A 2A R at these terminals have been shown to modify the amount and frequency of glutamate release (Marchi et al, 2002;Popoli et al, 2003) and extracellular glutamate outflow in various brain regions (Popoli et al, 1995;Corsi et al, 1999). Another important source of extracellular glutamate in the brain likely come from glial cells, as suggested by studies showing that astrocytes release large amounts of glutamate by physiological astrocytic calcium levels and by inversion of glutamate transporter activity during hypoxia (Haydon and Carmignoto, 2006).…”
Section: Discussionmentioning
confidence: 99%